Immunity in natural history - Rolston, Holmes, 1932-2025, author; University of Chicago Press, publisher (Colorado State University. Libraries, 1996)
Immunity, involving a struggle for health, is also the defense of biological identity, and, in advanced species, of an idiographic self. The identity of any such "self," though protected by immunity, is enlarged by kin selection, sexuality, reproduction, and caring for offspring. The environment "foreign" from the perspective of immunity is "home" from the perspective of ecology. Immunity makes evolution possible. Immunity, in which an organism acquires information during its biography, is the evolution of ordered control and results in values shared as well as selves defended. Errors here are intrinsic to trial and error learning, a process with analogies in the science of immunology.
Nobel Conference XXVIII. Lecture at Gustavus Adolphus College, October 1992.
Keywords: kin selection; selfish; self; immunity; ecology; natural history